PENGARUH GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Agustina, Monika (ABDI EQUATOR, 2025)
This study aims to examine the effect of green accounting implementation and environmental performance on company profitability. The data used comes from secondary data from the official website of the Indonesia Stock Exchange. The research sample amounted to 60 data from manufacturing companies in the food and beverage sub-sector selected using purposive sampling method. The results of the analysis show that environmental costs, as a measurement of green accounting, have no effect on corporate profitability. In line with this, environmental performance also shows the same results, namely not having an influence on company profitability. In simultaneous testing, both independent variables, namely green accounting and environmental performance, have a positive influence on the dependent variable, namely company profitability. The results of this study make an important contribution to understanding the impact of green accounting practices and environmental performance on the financial well-being of manufacturing companies in the food and beverage sub-sector.